Infantile-Onset Charcot–Marie–Tooth Disease With Pyramidal Features and White Matter Abnormalities Due to a De novo MORC2 Gene Variant: A Case Report and Brief Review of the Literature - Frongia, Ivana; Rizzi, Susanna; Baga, Margherita; Ceteroni, Laura Maria; Spagnoli, Carlotta; Salerno, Grazia Gabriella; Frattini, Daniele; Kaare, Milja; Pisani, Francesco; Fusco, Carlo (Frontiers in Neurology, 2021)
Background: Charcot Marie Tooth (CMT) is the most frequent group of inherited neuropathies and includes several heterogeneous phenotypes. Over 80 causative genes have been described so far. Variants in the Microrchidia family CW-type zinc finger 2 (MORC2) gene have been described in several axonal polyneuropathy (CMT2) patients with childhood or adult onset. Occasionally more complex phenotypes with delayed milestones, severe hypotonia, intellectual disability, dystonic postures, pyramidal signs and neuroimaging abnormalities have been reported (2, 7). Case presentation: we report on a patient with a de novo MORC2 gene variant (c.1181A>G p.Tyr394Cys) with a history of developmental delay, axial hypotonia, progressive gait disorder with dystonic features and intentional tremor. At the age of 8 years he showed bilateral pyramidal signs (clonus, increased tendon reflexes, Babinski sign) and bilateral pes cavus. The first neuroimaging performed at the age of 3 years, demonstrated white matter abnormalities in the posterior periventricular zone, in the frontal lobes bilaterally and at the midbrain, stable during childhood and adolescence. Nerve conduction studies (NCS) were negative until the age of 15 years, when a sensory axonal neuropathy appeared. The association between pyramidal signs and neuropathy due to MORC2 gene variant is increasingly being highlighted, although a neuroradiological correlate is evident only in about half of the cases. Longitudinal nerve conduction velocity (NCV) are helpful to identify late-onset features and provide useful information for diagnosis in patients with rare neurogenetic disorders. Conclusions: characterization of complex neurological disorders is important to delineate the expanding phenotypic spectrum of MORC2-related disease, to confirm if possible the pathogenicity of the variants and to deepen the genotype-phenotype correlation.